2006
DOI: 10.1098/rspb.2005.3450
|View full text |Cite
|
Sign up to set email alerts
|

MHC genes and oxidative stress in sticklebacks: an immuno-ecological approach

Abstract: Individual variation in the susceptibility to infection may result from the varying ability of hosts to specifically recognize different parasite strains. Alternatively, there could be individual host differences in fitness costs of immune defence. Although, these two explanations are not mutually exclusive, they have so far been treated in separate experimental approaches. To analyse potential relationships, we studied body condition and oxidative stress, which may reflect costs of immunity, in three-spined s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 57 publications
2
57
0
Order By: Relevance
“…In the present study, stream sticklebacks showed extremely high respiratory burst activity during the heat wave. Such high levels of respiratory burst activity are potentially harmful for the host itself, as oxygen radicals might lead to increased oxidative stress and self-tissue damage (Kurtz et al 2006(Kurtz et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, stream sticklebacks showed extremely high respiratory burst activity during the heat wave. Such high levels of respiratory burst activity are potentially harmful for the host itself, as oxygen radicals might lead to increased oxidative stress and self-tissue damage (Kurtz et al 2006(Kurtz et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is intimately linked to parasite resistance and fitness (Kurtz et al, 2006) and the removal of these free radicals is achieved through non-enzymatic and enzymatic reactions. The primary enzymatic antioxidant defence system is the glutathione redox system that reduces hydrogen peroxide and lipid hydroperoxides at the expense of oxidizing GSH to its disulfide form (GSSG).…”
Section: Discussionmentioning
confidence: 99%
“…This has contributed to the unclear role of ROS as moderators of sexually selected traits, and of carotenoids in countering their systemic effects on health in general and colour in particular (Hartley and Kennedy, 2004;Isaksson et al, 2007). The summed negative effects of ROS on aspects of immunocompetence have previously been measured (Kurtz et al, 2006), and one study has assessed the effects of lipid peroxidation in the context of sexual signalling (McGraw et al, 2005b). However, not a single study has to the best of our knowledge measured the circulating levels of ROS subsequent to antioxidant treatment and concomitant effects on colouration.…”
Section: Discussionmentioning
confidence: 99%